Mitigating negative impacts of heat stress in growing rabbits via dietary prodigiosin supplementation - Abdelnour, S.A.; El-Saadony, M.T.; Saghir, S.A.M.; Abd El-Hack, M.E.; Al-shargi, O.Y.A.; Al-Gabri, N.; Salama, A. (Livestock science, 2020)
•There is no available data of using secondary microbial metabolites in reducing the negative impacts of heat stress in rabbits.•Dietary prodigiosin supplementation enhanced the growth performance but had no effect on feed intake of heat stressed rabbits.•Prodigiosin (100mg/kg) improved the immune responses and oxidative status of rabbit exposed to heat stress and reduced significantly lipid peroxidation and inflammatory responses.•Prodigiosin as a natural and sustainable feed additive could reduce the negative impacts of heat stress on rabbit. The adverse influences of elevated ambient temperatures during the summer season on the rabbit industry have received increased global attention. Prodigiosin (PRG) is a natural pigment with powerful antioxidant activities. In this study, the aim was to explore the potential action of PRG for mitigating the negative impacts of heat stress in growing rabbits. A 120 growing rabbits (weaned, males, 35 days of age) were randomly allocated into four treatments of 30 rabbits each. The first group was received a basal diet without PRG (0 g/kg diet), and the 2, 3, and 4 groups received diets including PRG (50, 100, 150 mg/kg diet, respectively) for eight consecutive weeks during the summer season. Results showed that PRG improved significantly final body weight (FBW), daily body weight gain (DBWG), and feed conversion ratio (FCR), but did not affect feed intake (FI). Compared with the control, PRG addition with 50, 100, and 150 mg/kg diet decreased significantly total bilirubin (TB), triglycerides (TG), gamma-glutamyl transferase (GGT) and creatinine levels. The plasma levels of total antioxidant capacity (TAC) and glutathione in the group received (100mg/kg) diet were significantly higher than those in the other groups. Still, MDA was markedly reduced in PRG-treated groups compared with the control. Pro-inflammatory cytokines levels (interleukin-4 (IL-4) and Interferon gamma (IFNγ) were significantly decreased (P<0.001), but lysosome activity and nitric oxide levels were significantly increased (P<0.009) in rabbits fed diets containing PRG (100 and 150 mg/kg) compared with those in the control group. Pathological screening of liver tissues shown moderate to severe degenerative and necrotic alterations in rabbits exposed to thermal stress, which is enhanced with supplementation of PRG at different levels. The obtained results suggest that PRG as a novel feed additive could be effectively used to improve the growth and health status through enhancing immunity, and antioxidant features further reduce the inflammation cytokines of growing rabbits exposed to heat stress conditions.